Contamined lands: a Canadian perspective - Létourneau, Gilles; Chomyn, Beverley (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1991)
The existence of contaminated sites in Canada has become a problem of nation-wide concern. Actions at civil and common law based on the traditional requirements of showing that property interests have been affected or personal injury has resulted are inadequate to address widespread harms arising from pollution. At the national level programs and policies have been developed to address clean-up of contaminated sites. At the provincial level legislation is being developed, directed at making persons responsible for the pollution they cause. Nonetheless, there are shortcomings under the present system in matters concerning victim redress and clean-up and restoration of contaminated sites. Victims are still struggling to obtain redress and compensation, especially in cases of defendant bankruptcy. It may be necessary as in the U.S. to create a Superfund to ensure compensation when there are orphan sites or when the defendant has become insolvent. There may be merit in establishing at the Federal level and in the other provinces a class action scheme along the lines of the Quebec model with an Assistance Fund to help litigants. In addition, there is a need to develop in legislation comprehensive requirements of clean-up and restoration of contaminated sites, that can be applied consistently nation-wide.